Translation Projest: The Process in Making Good Translation Works - Anshori, Adam (Journal of English and Education (JEE), 2007)
Before we begin a translation work, we must think the process of making it as a whole. We must think all of the aspects which make a good translation. The first thing to do is establishing the project. Here, we will introduce with T4 (text, target, team, ^d tools). The next step will be Exegesis, Transferring Language and Writing the Draft, Evaluation Step, Result of Revision Draft and Consultation Step.